School District Superintendents as Transformational Leaders - Bjork, Lars G. (Advances in Social Sciences Research Journal, 2024)
The educational reform movement in the United States (1983-2024) presented school district superintendents with a wide array of challenges and opportunities. Initially, state and federal policymakers’ called for draconian school and district level accountability and endorsed he notion of top-down management. However, the reality of implementing district-wide, systemic changes focused on improving student learning outcomes influenced a shift in superintendents’ role from manager to teacher-scholar. During the last decade, researchers examined the role of superintendents in Instructionally Effective School Districts (IESD) and reported that they used their managerial prerogatives to initiate and sustain district-wide instructional improvement (Bjork, 2024). Research findings suggest that their involvement hiring and supervising teachers, evaluating principals, clearly articulating instructional and curricular goals, monitoring instructional improvement and, engaging in long-term financial planning for instruction indirectly influence the quality of learning and teaching. Findings from this longitudinal case study extend our understanding of how superintendents’ enact their role as teacher-scholar help to explain their success. Key elements of Transformational Leadership including idealized influence, inspirational motivation, intellectual stimulation and, individual consideration provided considerable insight into how they enacted their role. In addition, findings suggest that over time followers at different levels of the school district’s organization (teachers, principals and central office staffs) adopted Transformational Leadership dispositions and practices suggesting that it may be viewed as being both multidimensional and multi-directional. These findings may expand our understanding of how superintendents’ transformational leadership may influence the development of professional cultures and enhance student learning.